Imaginary differential equation!

Calculus Level 3

For the differential equation d y d x + i y = 2 sin ( x ) \dfrac{dy}{dx}+iy=2\sin (x) , with initial condition y ( 0 ) = 3 2 y(0)=\dfrac{3}{2} , find y ( π ) y(\pi) . If y ( π ) = a b + c π i y(\pi)=\dfrac{a}{b}+c\pi i , for co-prime integers a a and b b , find a b c abc .

Notation: i = 1 i = \sqrt {-1} denotes the imaginary unit .


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Jun 22, 2019

The given differential equation is the first-order ODE of the form d y d x + p ( x ) y = g ( x ) \dfrac {dy}{dx} + p(x)y = g(x) . We can use a multiplier μ ( x ) = e p ( x ) d x = e i d x = e i x \mu (x) = e^{\int p(x)\ dx} = e^{\int i \ dx} = e^{ix} . Then we have:

e i x d y d x + i e i x y = 2 e i x sin x By Euler’s formula: e i θ = cos θ + i sin θ d d x ( e i x y ) = 2 e i x ( e i x e i x 2 i ) = i ( 1 e 2 i x ) e i x y = i ( 1 e 2 i x ) d x = i x e 2 i x 2 + C where C is the constant of integration, y ( x ) = i x e i x e i x 2 + C e i x y ( 0 ) = 0 1 2 + C = 3 2 C = 2 y ( x ) = i x e i x e i x 2 + 2 e i x y ( π ) = i π e π i e π i 2 + 2 e π i By Euler’s formula: e ± π i = 1 = π i + 1 2 2 = 3 2 π i \begin{aligned} e^{ix} \frac {dy}{dx} + i e^{ix} y & = 2 e^{ix} \color{#3D99F6} \sin x & \small \color{#3D99F6} \text{By Euler's formula: } e^{i\theta} = \cos \theta + i\sin \theta \\ \frac d{dx} \left(e^{ix} y\right) & = 2 e^{ix} \color{#3D99F6} \left(\frac {e^{ix}-e^{-ix}}{2i}\right) \\ & = i \left(1 - e^{2ix}\right) \\ \implies e^{ix}y & = \int i \left(1 - e^{2ix}\right) dx \\ & = ix - \frac {e^{2ix}}2 + \color{#3D99F6} C & \small \color{#3D99F6} \text{where }C \text{ is the constant of integration,} \\ \implies y(x) & = ix e^{-ix} - \frac {e^{ix}}2 + Ce^{-ix} \\ y(0) & = 0 - \frac 12 + C = \frac 32 & \small \color{#3D99F6} \implies C = 2 \\ \implies y(x) & = ix e^{-ix} - \frac {e^{ix}}2 + 2e^{-ix} \\ y(\pi) & = i \pi e^{-\pi i} - \frac {e^{\pi i}}2 + 2e^{-\pi i} & \small \color{#3D99F6} \text{By Euler's formula: } e^{\pm \pi i} = - 1 \\ & = - \pi i + \frac 12 - 2 \\ & = - \frac 32 - \pi i \end{aligned}

Therefore, a b c = 6 abc = \boxed 6 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...